RELATIONSHIP OF GRIT AND RESILIENCE WITH PSYCHOLOGICAL WELL-BEING AMONG YOUNG FOOTBALL PLAYERS - Kaur, Dr. Guneet Inder Jit (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
Abstract. Grit and resilience form the psychological concepts that are referred to as indices of mental fortitude and essential contributors to psychological well-being. Mental fortitude is an important facilitator of sports excellence which requires a wealth of mental strength to be functioning at optimal levels in stressful and demanding environments like the dynamic environment of team game of Football. Football is highly organized and competitive sport and India has been one of the youngest sporting nations in Football. The team sports form a social institution designed to help improve the health and wellness of the athletes and provide an opportunity for positive youth development. Thus, these young football athletes are not miniature elite athletes; they are a distinct client group to whom sport psychology practitioners (SPPs) increasingly deliver services. Unfortunately, the lacuna of research pertaining to the young athletes becomes a deterrent in the needs assessment of the young athletes. Therefore, the goal of the current research was to understand the psychological profile of young football players through investigating the relationship of grit and resilience and their impact on wellbeing. The sample included 35 young football players from Bangalore. The inter correlation between the three variables was assessed. As grit, resilience and psychological well-being are the distinguishing factors of top performers in every field, their significant inter relationships have clarified the psychological profile of the young athletes. This understanding of psychological profile has implications on designing mental training modules for young football players.